(untitled) (AGROINNOVATSIYА, 2024)
This article presents information on the growth development and medicinal properties of Greek shambalas (Trigonella foenum-graecum L.) in Surkhandarya region, which is an annual leguminous fodder and the oldest used medicinal herb and traditional spice. is a plant. This review presents a preliminary observation and analysis of the growth, development, fertility, and medicinal properties of Greek Shambala. The relationship between the physical properties of seeds and the influence of selected cultivation measures (planting of seeds, chemical protection of plants) on the division of seeds into homogenous groups is discussed. Fenugreek extract and its bioactive compounds have been shown to exhibit excellent antidiabetic and antiobesity activity in animal and human studies. It is taken into account that the scientific research conducted in Uzbekistan on the productivity and medicinal properties of Greek shambala is insufficient.